(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Uzbekistan’s water resource management faces unprecedented challenges due to the complex interplay of climate change, aging infrastructure, population growth, and transboundary water dependencies. This article provides a comprehensive assessment of how modernization—both engineering and institutional—can enhance the resilience and sustainability of Uzbekistan’s water systems in a rapidly changing climate. Drawing on empirical data, scenario modeling, and global best practices, the study identifies critical vulnerabilities in current management structures and proposes a suite of innovative adaptation strategies. The research underscores the importance of integrated approaches that combine technical upgrades, digitalization, policy reform, and stakeholder engagement to secure water for agriculture, industry, and urban populations. Recommendations are offered to guide policymakers, engineers, and researchers in ensuring water security for Uzbekistan amid 21st-century uncertainties.